Gallic acid alleviates visceral hyperalgesia following maternal separation in mice by inhibiting EphrinB2/EphB2 signaling mediated activation of neurons and glial cells - Guo, Shu-fen; Wang, Yu; Zheng, Han; Tu, Hong-qin; Xi, Yu-qing; Li, Dan; Ma, Zheng-liang; Zhang, Wei; Ruan, Jia-ping (Frontiers in Immunology, 2025)
BackgroundEarly life stress (ELS) causes functional gastrointestinal issues linked to visceral hyperalgesia. Activation of spinal neurons and glial cells is key to the development and persistence of visceral hyperalgesia. Our previous research has shown that EphrinB2/EphB2 signaling in the spinal cord facilitates this hyperalgesia through neuron and glial cell activation. Gallic acid (GA), a natural compound with recognized anti-inflammatory and analgesic effects, may attenuate visceral hyperalgesia. This study investigates whether GA mitigates visceral hyperalgesia induced by ELS in mice via inhibiting EphrinB2/EphB2-mediated activation of neurons and glial cells.MethodsWe employed a maternal separation (MS)-induced ELS model and recorded abdominal withdrawal reflex (AWR) scores following colorectal distension (CRD) in adult mice. Molecular docking analysis was used to evaluate the binding stability of GA with the EphrinB2-EphB2 complex or EphrinB2 alone. After CRD, we assessed EphrinB2 and EphB2 expression, glial and neuronal activation, and synaptic plasticity in the spinal cord of MS mice, with or without GA treatment. C-fos levels were measured via immunohistochemistry, and protein expression was quantified by Western blotting. EphrinB2/EphB2 co-expression with neurons or glial cells was examined by double-labeling, and a 3D reconstruction confirmed cell type-specific expression.ResultsMolecular docking confirmed that GA binds stably to EphrinB2-EphB2 complex or EphrinB2 alone. In adult MS mice, CRD stimulation induced pain behaviors, accompanied by substantial activation of spinal neurons and glial cells, as well as upregulation of synaptic N-methyl-D-aspartate receptors (NMDARs). EphrinB2 and EphB2 were localized within spinal astrocytes, microglia, and neurons. Furthermore, exogenous EphrinB2 induced the activation of glial cells and neurons, NMDARs phosphorylation, and visceral hypersensitivity in naive mice. Intraperitoneal injection of GA can alleviate the above conditions.ConclusionsOur findings suggest that spinal EphrinB2/EphB2 signaling is crucial in the development of maternal separation-induced visceral hyperalgesia. GA may alleviate hyperalgesia by inhibiting the EphrinB2/EphB2 signaling pathway, thereby modulating nociceptive processing by MS.